The Effect of Squeeze Casting Process on Mechanical and Micro-structural Properties of Magnesium AZ31 - Tri Cahyo Wahyudi; Tarkono Tarkono; Irza Sukmana; Fauzi Ibrahim; Yanuar Burhanuddin; Fethma M Nor (AVIA, 2022)
The amount of damage that occurs in various cases of fractures in the bone, both accidents and other events is increasing, it is necessary to have materials which are natural or artificial that can interact with the body system with the aim of repairing, restoring and replacing damaged tissue or as a network connector. body. The use of magnesium as a biodegradable stent material is also based on a fixed tissue structure which is an important element in the body's organs, magnesium is also considered a non-carcinogenic element. The results of the implantation of the stent material that the mechanical properties of the material can survive during the implantation process without showing failure. The parameters used in this research, The sample used is a material that has been squeezed through the squeeze casting process with each pressure variation of 250 MPa, 350 MPa, 500 MPa and 550 MPa at a temperature of 4000C for a pressing time of 1 minute, with a holding time of 5 minutes and argon gas pressure of 1 bar. . In this study it can be concluded that the variation of pressure greatly affects the results of the level of hardness. In this test, it can be seen that the higher the pressure, the greater the hardness value. The highest value is found at a pressure of 550 MPa at 51 HRV, and the highest maximum stress value is 128.26 MPa, this value is close to the tensile strength of the mechanical properties of the cortical and concelues bone. with a holding time of 5 minutes and argon gas pressure of 1 bar. In this study it can be concluded that the variation of pressure greatly affects the results of the level of hardness. In this test, it can be seen that the higher the pressure, the greater the hardness value. The highest value is found at a pressure of 550 MPa at 51 HRV, and the highest maximum stress value is 128.26 MPa, this value is close to the tensile strength of the mechanical properties of the cortical and concelues bone. with a holding time of 5 minutes and argon gas pressure of 1 bar. In this study it can be concluded that the variation of pressure greatly affects the results of the level of hardness. In this test, it can be seen that the higher the pressure, the greater the hardness value. The highest value is found at a pressure of 550 MPa at 51 HRV, and the highest maximum stress value is 128.26 MPa, this value is close to the tensile strength of the mechanical properties of the cortical and concelues bone.